The Humanist Latin authors of Croatia and the Foundations of Contemporary Europe - Jovanović, Neven (2009)
A short description of the corpus of Croatian Neo-Latin literature, its place and role in European heritage, its highlights and possibilities of its exploration. A presentation of the Croatian Latin authors digital collection (Croatiae auctores Latini, CroALa).